PENERAPAN PENERAPAN MODEL PEMBELAJARAN WORD SQUARE DALAM UPAYA PENINGKATAN HASIL BELAJAR MATEMATIKA - Ratna Natsir (Prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Muhammadiyah Parepare, 2025)
This study aims to improve learning outcomes math class VII students of SMP Negeri 1 Parepare through the application of learning models Word Square. Subjects in this study is class VIII8 students of SMP Negeri 1 Parepare 47 in total learners. This study was conducted in two cycles each lasting 4 meetings and implemented test every cycle end of the cycle. Data collection was performed using achievement test and observation. The collected data were analyzed using quantitative and qualitative analysis. The results quantitatively indicating that an increase in mathematics achievement class VIII students of SMP Negeri 1 Parepare through the application of learning models Word Square. It can be seen from the results of learning in the first cycle the number of students who pass the study only 47 people with an average score of 75 and the second cycle the number of students who pass the study there were 46 students from 47 students with an average score of 82, 77. In the second cycle occurred in the classical mastery learning which is 100% of the number of students who achieve a score of at least 65% of the ideal score. While qualitatively during the learning process with the application mode pembelajaranl Word Square seen a change in attitude from the increasing activity of learners from the first cycle to cycle II. The results of this study it can be concluded that an increase in student learning outcomes math class VIII Junior High School 1 Parepare with the application of learning models word Square.